Nature of Emotion Categories: Comment on Cowen and Keltner. Issue 2 (February 2018) - Barrett, Lisa Feldman; Khan, Zulqarnain; Dy, Jennifer; Brooks, Dana
Abstract : Cowen and Keltner (2017) published the latest installment in a longstanding debate about whether measures of emotion organize themselves into categories or array themselves more continuously along affective dimensions. We discuss several notable features of the study and suggest future studies should consider asking questions more directly about physical and psychological variation within emotion categories as well as similarities between categories.